1994
DOI: 10.1007/bf02950787
|View full text |Cite
|
Sign up to set email alerts
|

An XRF study of trace elements accumulation in kidneys of tumor-bearing mice after treatment withcis-DDP with and without selenite and selenocistamine

Abstract: The effect of cis-DDP treatment with and without selenite and selenocistamine was studied on kidneys of tumor-bearing mice. The amounts of cis-DDP, selenite, and selenocistamine injected were chosen so as to be compatible with the treatment of humans. The animals were sacrificed at 7, 14, and 28 d after treatment. The kidneys were removed and subjected to trace element analysis by a novel X-ray fluorescence (XRF) method and for pathological assessment. The results show that following treatment with cis-DDP, K,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In animals, treated with CP for tumours, increased levels of trace elements, for example, iron, copper, and zinc, in addition to platinum, were observed in the kidneys and liver. This suggested that platinum toxicity is due to an overall accumulation of trace elements in these organs and is attributable to platinum alone [6]. …”
Section: Introductionmentioning
confidence: 99%
“…In animals, treated with CP for tumours, increased levels of trace elements, for example, iron, copper, and zinc, in addition to platinum, were observed in the kidneys and liver. This suggested that platinum toxicity is due to an overall accumulation of trace elements in these organs and is attributable to platinum alone [6]. …”
Section: Introductionmentioning
confidence: 99%
“…In animals, treated with cisplatin for tumours, increased levels of trace elements, e.g., iron, copper, and zinc, in addition to platinum, were observed in the kidneys and liver (XRF technique with Mo X-ray tube and a SiLi detector). This suggested that platinum toxicity is due to an overall accumulation of trace elements in these organs and attributable to platinum alone (Shenberg et al , 1994). It has also been shown that trace element levels in blood, liver, and kidneys were different between tissue samples obtained from tumour mice and normal mice (Feldstein et al , 1998).…”
Section: Overview Of In Vitro Xrf Applications In Medicinementioning
confidence: 99%
“…Generally, DNA damaging agents have less toxicity on nonproliferating cells, yet the proximal tubule cells are selectively damaged by CIS because of its accumulation in the kidney to a greater extent compared to other organs [5]. Suggests that this injury is due to inflammation, oxidative stress and apoptosis [6].…”
Section: Introductionmentioning
confidence: 99%